Frailty Trajectories After Treatment for Coronary Artery Disease in Older Patients. (May 2016) - Freiheit, Elizabeth A.; Hogan, David B.; Patten, Scott B.; Wunsch, Hannah; Anderson, Todd; Ghali, William A.; Knudtson, Merril; Maxwell, Colleen J.
Abstract : Background—: Frailty is an independent risk factor for cardiovascular outcomes. However, its trajectory after coronary artery disease treatment is unknown. Methods and Results—: Three hundred seventy-four patients undergoing nonemergent cardiac catheterization followed by treatment (ie, 128 coronary artery bypass graft [CABG], 150 percutaneous coronary intervention [PCI], 96 medical therapy only) were observed for 30 months. A frailty index (FI) score was calculated at baseline (before initial treatment) and 6, 12, and 30 months after treatment. Random-effects models compared FI score trajectories by sex, age, and treatment group. Mean baseline FI scores were 0.170, 0.154, and 0.154 for CABG, PCI, and medical therapy only, respectively. FI scores decreased (improved) 6 months after initial treatment, then increased (worsened) at 12 and 30 months ( P <0.001 for differences over time). Women had nonsignificantly higher FI scores than men ( P =0.097) but followed the same trajectory ( P =0.352 for differences over time). In patients aged ≥75 years, FI scores increased postbaseline for CABG and medical therapy only and after 6 months for PCI patients. Patients <75 years assigned to PCI and CABG experienced a sustained frailty reduction, whereas those assigned to medical therapy only showed stable frailty over the 30-month follow-up period ( P value for differences over time by age and treatment group=0.041). Conclusions—: With coronary artery disease treatment, frailty generally follows a U-shaped trajectory, but the pattern may differ by age and treatment. Further investigation is needed to confirm these observations and determine whether patients might benefit from consideration of frailty status. Abstract : Supplemental Digital Content is available in the text.